A Contextual Factors Framework to Inform Implementation and Evaluation of Public Health Initiatives. (September 2017) - Vanderkruik, Rachel; McPherson, Marianne E.
Evaluating initiatives implemented across multiple settings can elucidate how various contextual factors may influence both implementation and outcomes. Understanding context is especially critical when the same program has varying levels of success across settings. We present a framework for evaluating contextual factors affecting an initiative at multiple phases of its life cycle, including design, implementation, scale-up, spread, and sustainability. After providing a brief overview of related frameworks from the fields of improvement science and implementation science and of the methods by which we drew from this literature to develop the current framework, we present how this framework was customized and applied to three national public health initiatives. We close with implications for how evaluators can apply the framework to facilitate a deeper understanding of a program's implementation and success, collaborate with project stakeholders, and facilitate sustainability, spread, and scale-up of public health initiatives.